COMBINED INFLUENCE OF POST-REFORMER TEMPERATURE AND RED MUD CATALYST ON THE THERMOCATALYTIC REFORMING (TCR®) OF DIGESTATE - Onyishi, Hillary; Neidel, Johannes; Daschner, Robert; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2024)
This work studies the combined effect of increasing the post-reformer temperature and introducing red mud as a support catalyst in the thermocatalytic reforming (TCR®) of digestate. The TCR®, developed by the Fraunhofer UMSICHT, is an extension and improvement of pyrolysis. In other words, the products of the TCR®, especially the biooil, has been shown to be more thermally stable and, therefore, more applicable than the products of pyrolysis. However, optimisation of the process is necessary for achieving commercialisation of the process. The crux of the optimisation process is the investigation of factors influencing the product yield and quality. Two of those factors are the post-reformer temperature and the catalyst in the post-reformer. Normally the biochar from the feedstock acts as the catalyst but in this study a support or secondary catalyst, red mud, a solid waste from the processing of bauxite, has been added. The post-reformer temperatures used are 600 °C and 750 °C. The results show that increase in the post-reformer temperature increases the gas yield as well as the hydrogen fraction of the gas and reduces the yields of the other products. Meanwhile, addition of red mud as a support catalyst also increases the hydrogen fraction of the gas, even when the gas yield does not increase. This influence of the red mud is seen to be more pronounced at 600 °C, suggesting it can be used to minimise the energy requirement of the process. Overall, the addition of red mud increases the yields of the liquid and gaseous products and reduces the yield of the solid product, although it has little or no influence on specifically the yield of the biooil. Nevertheless, both methods improve the quality of the oil. Finally, the quality of the product water tends to improve in both cases. Therefore, this work establishes a pathway for the valorisation of both digestate and red mud.
CRIS-Team Scopus Importer:2024-12-06
Keywords: digestate.; hydrogen; pyrolysis; red mud; thermocatalytic reforming